2021
DOI: 10.1038/s41388-021-01912-4
|View full text |Cite
|
Sign up to set email alerts
|

SFPQ promotes an oncogenic transcriptomic state in melanoma

Abstract: The multifunctional protein, splicing factor, proline- and glutamine-rich (SFPQ) has been implicated in numerous cancers often due to interaction with coding and non-coding RNAs, however, its role in melanoma remains unclear. We report that knockdown of SFPQ expression in melanoma cells decelerates several cancer-associated cell phenotypes, including cell growth, migration, epithelial to mesenchymal transition, apoptosis, and glycolysis. RIP-seq analysis revealed that the SFPQ-RNA interactome is reprogrammed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 72 publications
1
13
0
Order By: Relevance
“…This screening approach highlights an underused approach to targeted therapeutic interference in BRAF -mutant colorectal cancer cells by exploiting the essential nuclear programs induced by MAPK activity identified in thyroid cancer cell lines. Consistent with the results in colon cancer cell lines, low expression of SFPQ is associated with decreased survival probability in The Cancer Genome Atlas (TCGA) dataset [ 54 ]. Further investigation of the role of SFPQ in the context of BRAF V600E -mutant thyroid cancer cells is required.…”
Section: Braf Mutation and Sdlsupporting
confidence: 82%
“…This screening approach highlights an underused approach to targeted therapeutic interference in BRAF -mutant colorectal cancer cells by exploiting the essential nuclear programs induced by MAPK activity identified in thyroid cancer cell lines. Consistent with the results in colon cancer cell lines, low expression of SFPQ is associated with decreased survival probability in The Cancer Genome Atlas (TCGA) dataset [ 54 ]. Further investigation of the role of SFPQ in the context of BRAF V600E -mutant thyroid cancer cells is required.…”
Section: Braf Mutation and Sdlsupporting
confidence: 82%
“…The association between organ carcinogenesis and AMIGO2 expression has been reported in various types of cancer, including gastric cancer [ 13 , 14 ], pancreatic cancer [ 20 ], colorectal cancer [ 11 , 19 ], breast cancer [ 12 ], ovarian cancer [ 17 ], endometrial cancer [ 21 ], melanoma [ 15 , 16 , 40 ], and pituitary neuroendocrine tumors [ 18 ]. Since AMIGO2 expression is involved not only in tumor development but also in tumor progression including acquisition of metastasis, AMIGO2 may be a new molecule that controls cancer stem cell-like function.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, transcriptionally high levels of AMIGO2 are associated with shortened survival of patients with CRC [ 11 ], breast cancer [ 12 ], and gastric cancer [ 13 ]. AMIGO2 has been reported as a novel pathogenesis-related gene in gastric cancer [ 14 ], melanoma [ 15 , 16 ], ovarian cancer [ 17 ], and pituitary neuroendocrine tumors [ 18 ]. In addition, bioinformatics analysis using the transcriptome database selected AMIGO2 as a cancer-related gene candidate for CRC [ 19 ], pancreatic cancer [ 20 ], and endometrial cancer [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, various experimental systems demonstrated that the direction and mechanisms by which PSF/ncRNA complexes affect oncogenic pathways are cell type-dependent. [61][62][63][64][65] Similarly, notwithstanding the role of NEAT1 and PSF in inflammation and activation of the innate immune response [24,[66][67][68][69], paraspeckles' effects on viral infection are pathogen-specific. [24,57,64,[70][71][72][73][74][75] Based on the multiple mechanism by which PSF mediates its functions, it is difficult to predict the effects of VL30 mRNA expression on inflammatory (e.g., cytokine release) or oncogenic pathways in human T-cells.…”
Section: Discussionmentioning
confidence: 99%